Direito à literatura e formação de professores e leitores literários: o caso do Pet PedPalmas/UFT - Barbosa, Eleny Silva (Universidade Federal do Tocantins, 2025)
This Dissertation, linked to the Postgraduate Program in Education (PPGE), at the Federal University of Tocantins (UFT), Palmas University Campus, Research Line: State, Society and Educational Practices, addresses the theme of initial and continued training of teachers, the right to literature and the training of literary readers. The focus of the study is the Right to Literature Project of the Tutorial Education Program of the Pedagogy Course at the UFT Palmas Campus (PedPalmas), a teaching, research and extension activity, developed since 2021. It aims to understand the Right to Literature Project Literature, a teaching, research and extension activity by PET PedPalmas, as a strategy for training apprentice teachers in the training of literary readers in the early years of elementary school. The study is based on theoretical-documentary contributions, constituting a research of the bricoleur or quilt maker type (Denzin; Lincoln, 2006), an attribute of the qualitative paradigm (Chizzotti, 2014). It uses studies that are related to the theme of the Right to Literature Project, such as initial teacher training (Freire, 2011), training of literary readers (Cândido, 2011; Todorov, 2009), among others; and addresses the Project itself as an object of investigation (UFT, 2007, 2022). In this way, it shares the new outlines of teacher training and literary literacy studies, for interdisciplinary teacher training, by Girotto and Souza (2010), for teaching reading strategies, and by Cândido (2011), with regard to right to literature. It is concluded that the activities promoted by the extension project provide scholarship holders with a more mature vision regarding the teaching profession. The dialogue established with experienced professionals contributes significantly to the development of a broader understanding of the social context, going beyond what the university, alone, would be capable of providing.